Efficacy and safety of bevacizumab in combination with irinotecan and capecitabine in first-line treatment of metastatic colorectal cancer - Jungić, Saša M; Tubić, Biljana; Gajanin, Radoslav; Gojković, Zdenka; Rakita, Ivanka (Vojnosanitetski pregled, 2017)
Background/Aim. The efficacy and safety of bevacizumab (BEV) in combination with capecitabin and irinotecan in first-line therapy for patients with metastatic colorectal cancer (mCRC) were studied. In order to improve safety and efficacy of chemotherapy, as well as to reduce adverse reactions to a minimum, doses of active agents applied were changed in relation to previously employed schedules. Methods. Patients with histologically documented mCRC with no previously received chemotherapy or with received adjuvant or neoadjuvant chemotherapy, which ended 6 months before capecitabin treatment (1000 mg/m2 per os from the 2nd to 8th day of each cycle), irinotecan (175 mg/m2 iv every 2 weeks), plus bevacizumab (5 mg/kg iv every 2 weeks) were observed. Results. This prospective study included 35 patients of both sexes. The overall response rate (ORR) of 28.6%, partial response (PR) of 28.6%, progressive disease (PD) of 28.6% and stable disease (SD) of 42.8% were found. The progression-free survival (PFS) of the analyzed patients was 11.3 (95% CL: 9.1–12.9) months while overall survival (OS) of the included patients was 25.2 (95% CL: 17.4–28.4) months and 117 adverse effects were recorded in 24 patients. Alopecia, nausea and vomiting, hemorrhage, hand-foot syndrome, diarrhea, abdominal pain, proteinuria, and hypertension (51.4%, 37.1%, 37.1%, 25.7%, 22.8%, 20.0%, 20.0% and 17.1%, respectively) were most frequently observed adverse effects. Conclusion. The results of this clinical trial support and recommend the use of bevacizumab plus capecitabin and irinotecan in the doses and schedule applied throughout this study as the first-line treatment of mCRC patients.
Keywords: colorectal neoplasms||; ||colorectal neoplasms; neoplasm metastasis||; ||neoplasm metastasis; antineoplastic combined chemotherapy protocols||; ||antineoplastic combined chemotherapy protocols; drug toxicity||; ||drug toxicity